A mixed-methods study protocol on factors contributing to suicide clusters among Native American youth in a northern plains reservation - Brockie, Teresa; Kahn-John, Michelle; Mata Lopez, Laura; Bell, Eleesha; Brockie, Truth; Brockie, Terry; Decker, Ellie; Glass, Nancy; Has Eagle, Hannah; Helgeson, Kenneth; Main, Nona J.; Kazemi, Mina; et al. (Frontiers in Public Health, 2024)
Introduction Suicide and suicide clusters within Native American Reservation communities are devastating to the entire community and increase individuals’ risk for suicide over the lifespan. The objective of this paper is to describe the Indigenous community-based participatory research protocol implemented in partnership with the Fort Belknap Indian Community in Montana, United States. The study protocol was developed to understand suicide risk and protective factors, and community-derived solutions, in a reservation community with history of a suicide cluster and high rates of youth suicide. Methods In this mixed-methods study, qualitative data from youth, adults, and service providers and quantitative data from 200 adolescents and young adults (aged 14–24 years) were collected in Fort Belknap, Montana from May – December of 2022. Qualitative data were collected first via in-depth interviews and focus groups. Survey questions included validated and pre-tested measures of factors youth experience across socio-ecological levels. Thematic analysis was applied to the qualitative data; and logistic regression models were used to examine relationships within the quantitative data. Discussion This study will add a multi-dimensional perspective to our current understanding of (1) risk and protective factors for suicide, community-derived postvention solutions, and insights on community assets, and (2) the current health and psychosocial status of youth in the Fort Belknap community. This study may serve as an exemplar of co-created, culturally safe solutions designed to address mental health resource gaps. Next steps include development of a suicide crisis response tool kit and a culturally aligned postvention intervention that will enhance individual, family, and community survivance.